Bioactive fatty acids as dietary supplements for farmed fish: effects on growth performance, lipid metabolism, gene expression and immune parameters - Kennedy, Sean Robert (University of Stirling, 2007)
Current feed formulations within the aquaculture industry have tended to rely on high dietary lipid thus offsetting relatively expensive protein as a source of energy. In this way, protein can be ‘spared’ for synthesis of new tissue and the high lipid content can also fulfil both fish and consumer essential fatty acid (EFA) requirements. However, the main disadvantage of feeding high lipid levels to farmed fish is a surplus of fat deposition in the flesh and other important tissues, which can detrimentally impact on quality characteristics central to the human consumer. However, based on previous work in other animal models, it is entirely feasible that supplementation of the diet with bioactive fatty acids such as conjugated linoleic acid (CLA) and tetradecylthioacetic acid (TTA) may mitigate the deleterious effects of feeding farmed fish high fat diets by reducing fat deposition in particular. The general objective of this research work was to test the hypothesis that CLA and/or TTA could augment growth, reduce fat deposition and enhance fatty acid composition via incorporation of these bioactive fatty acids, and increase n-3 highly unsaturated fatty acid (HUFA) levels in the flesh of commercially important fish species such as Atlantic salmon (Salmo salar), Atlantic cod (Gadus morhua L.) and rainbow trout (Oncorhynchus mykiss). This project also considered the influence of CLA and TTA on enzymes and transcription factors thought to be pivotal in lipid metabolism and fatty acid oxidation in particular. A subsidiary aim of this research work was to investigate the immunological impact of dietary CLA and TTA administration in these fish. The results of this project have revealed that the hypothesis was only partly proved. There was no effect in growth or biometry after either CLA or TTA supplementation in any of the fish species investigated. Additionally, there were few physiologically significant effects on fat levels on fish as a result of TTA or CLA administration. However, there were a number of effects on ...